Understorey productivity of selected medicinal herbs in major land management systems in humid tropical Kerala - Kunhamu, T.K.; Niyas, P.; Anwar, M.F.; Jamaludheen, V.; Raj, A.K. (Indian Journal of Agroforestry, 2020)
A field study was conducted in the humid tropical Kerala, India to evaluate the performance of understorey herbaceous medicinal crops viz. Zingiber officinale, Curcuma longa and Kaempferia galangal when intercropped with major land management systems in the humid peninsular India such as mature plantations of coconut, cashew, rubber and homegarden. These landuse systems by virtue of spatial and temporal advantages offer good scope for integrating shade tolerant crops and thereby offer supplementary returns to the farmer. The intercrop growth considerably varied among the land use systems both in vegetative growth and rhizome yields. Except turmeric yields under cashew all other crops showed reduction in yield under various systems as compared to treeless open. Ginger biometric growth was better under homegarden during early growth phase while the dry rhizome yield was considerably lower compared to coconut, cashew and rubber. Understorey productivity for ginger in terms of rhizome yield at final harvest followed the order treeless open (3.45 Mg ha-1), coconut (2.86 Mg ha-1), cashew (2.63 Mg ha- 1), rubber (2.60 Mg ha- 1) and homegarden (1.49 Mg ha-1). Turmeric rhizome production showed considerable variation with highest rhizome yield from mature cashew plantation (7.63 Mg ha-1) followed by open area (7.01 Mg ha-1) and the lowest from homegarden (1.77 Mg ha-1). Highest Galangal yields were reported from the treeless open (3.05 Mg ha-1) while homegarden recorded the lowest production (2.04 Mg ha-1). Intercrop yield for galangal was highest under cashew (2.95 Mg ha-1) followed by rubber (2.91 Mg ha-1) and coconut (2.15 Mg ha- 1). Understorey photosynthetically active radiation (PAR) transmittance presumed to have a cardinal influence on intercrop growth which was highest under cashew (75%), followed by rubber (58%), coconut (17%) and lowest under homegarden (7%). Turmeric and galangal showed strong positive correlation with understorey PAR. Regression equation relating PAR with rhizome yields showed statistical soundness with high coefficient of determination (R2) values (0.80 to 0.92). Linear, quadratic and logarithmic models were the best predictors of understorey productivity for the selected intercrops. Results suggest the vast opportunity for successful integration of shade tolerant, commercially important intercrops under mature agricultural land management systems prevalent in the tropics.